Safer nuclear energy through a higher degree of internationalisation? International involvement versus national sovereignty - Pelzer, Norbert (OECD Publishing, 2013)
On 11 March 2011, the Fukushima Daiichi nuclear accident occurred.1 In responding to this accident, the Director General of the International Atomic Energy Agency (IAEA) on 30 March 2011, with broad support by the IAEA Member States, called for a Ministerial Conference on Nuclear Safety which took place in Vienna from 20-24 June 2011.2 On 20 June 2011, the Conference adopted a Declaration on Nuclear Safety, which, inter alia, expresses sympathy and solidarity with Japan and emphasises "the importance of implementing enhanced national and international measures to ensure that the highest and most robust levels of nuclear safety are in place, based on the IAEA safety standards, which should be continuously reviewed, strengthened and implemented as broadly and effectively as possible and commit to increase bilateral, regional and international cooperation to that effect."3 The declaration furthermore requested the Director General of the IAEA to prepare a report and to draft an action plan building on the declaration and on the outcome of the ministerial conference